Samples spiked with pituitary-derived thyroid-stimulating hormone may disguise the extent of differences between thyroid-stimulating hormone assays. (November 2021) - Kalaria, Tejas; Fenn, Jonathan; Sharrod-Cole, Hayley; Sanders, Anna; Ford, Clare; Gama, Rousseau
Background: A large discordance in the diagnosis and potential management of hypothyroidism using Abbott and Roche thyroid assays has been reported recently. The difference in Abbott and Roche thyroid-stimulating hormone (TSH) results in these studies was larger than anticipated from the external quality assessment (EQA) reports. Methods: Abbott and Roche TSH method means in UK NEQAS for thyroid hormones distributions 430 to 454 were compared against the amount of TSH spiked. A TSH deplete serum pool was spiked with various concentrations of pooled high TSH serum and 3rd WHO International Standard for TSH (WHO-IS). Four serum pools with TSH close to clinical decision limits were spiked with two concentrations of WHO-IS. Results: On review of EQA data, median (IQR) Roche: Abbott TSH ratio was lower ( p < 0.001) in 48 pools spiked with TSH (1.11 (1.07–1.16)) compared to 41 pools not spiked (1.29 (1.25–1.31)) and the decrease was proportionate to the contribution of spiked TSH to total TSH in the samples (ρ=−0.908, p < 0.001). In spiking experiments, the relationship of Roche and Abbott TSH was different in TSH deplete pool spiked with WHO-IS (RocheTSH=1.13*AbbottTSH–0.52) and high TSH serum (RocheTSH=1.43*AbbottTSH–0.50), respectively. The Roche: Abbott TSH ratio decreased and the method agreement improved on spiking serum pools with WHO-IS. Conclusion: Abbott and Roche TSH assays are not in harmony in human serum samples but the agreement was better in samples spiked with WHO-IS which contains pituitary-derived TSH. Use of pituitary-derived TSH spiked samples, such as provided by EQA schemes, may mask clinically significant between-assay differences.